Alkaloid, Sterol and Triterpenoids from Glycosmis pentaphylla (Retz.) DC (Dhaka University Journal of Pharmaceutical Sciences, 2015)
Four compounds were isolated from the methanol extract of leaves of Glycosmis pentaphylla. The structures of the isolated compounds were solved as epi-oleanolic acid (1), ?-amyrin (2), spinasterol (3) and arborinine (4) by extensive spectroscopic studies, including high field NMR analyses as well as co-TLC with authentic samples. This appeares to be the first report of their occurrence from Glycosmis species. DOI: http://dx.doi.org/10.3329/dujps.v13i2.21887 Dhaka Univ. J. Pharm. Sci. 13(2): 115-118, 2014 (December)